Adherence of patients with diabetic macular oedema to intravitreal injections: A systematic review. (2nd November 2020) - Rose, Monique A.; Vukicevic, Meri; Koklanis, Konstandina
Abstract: The purpose of this study was to review adherence rates to intravitreal injections in the treatment of diabetic macula oedema and to identify factors associated with adherence. A systematic search of Embase, Medline, PsycINFO and CINAHL was conducted up to May 2020. Two authors independently screened, selected and appraised the studies. Seven articles on anti‐VEGF treatment were found to meet the inclusion criteria. No studies were found on intravitreal corticosteroids or dexamethasone implants. Attendance rates varied between studies from 35% to 85%. The rate of missed or delayed attendance ranged from 14% to 51%, whereas 25% of patients were lost to follow‐up at 12 months. Non‐adherence was found to be multifactorial and included patient related reasons, demographic characteristics and clinical factors. Enablers to adherence included patient understanding of the disease and treatment. Further research in this area is warranted in order to better understand adherence in these patients and to improve patient outcomes.